The Experiences of Women Working as Srathi Within the Gender Ideology of Balinese Hindu Society as a Resource for Social Studies Instruction at Penebel State Junior High School 1 - I Putu Wisnu Saputra; Luh Putu Sendratari; Sukadi Sukadi (Eduvest - Journal of Universal Studies, 2026)
The strong gender ideology within Balinese Hindu society influences the division of roles, power relations, and life experiences of women, including those who serve as Srathi. This study is motivated by the need to understand these lived experiences in the context of gender dynamics. This research aims to examine the experiences of women who work as Srathi within the dynamics of gender ideology in Balinese Hindu society and to explore its relevance as a source for social studies instruction at State Junior High School 1 Penebel. This qualitative phenomenological study explored the lived experiences of Srathi women in Mengesta Village through observations, in-depth interviews, and documentation studies involving Srathi women, village leaders, and social studies teachers. Data validity was ensured through triangulation, and analysis followed the Miles and Huberman model. This study employs Louis Althusser's theory of ideology, Anthony Giddens' structuration theory, Betty Friedan's liberal feminism theory, Simone de Beauvoir's existentialist feminism theory, and Dorothy Smith's standpoint theory. The results of this study indicate that the underlying motives of Mengesta Village women in carrying out their roles as Srathi are driven by economic motives, familial encouragement, community subjectivity, and traditional obligations. The experiences of Mengesta Village women who become Srathi can further be categorized into sekala experiences encompassing triple roles, marginalization, and resistance and niskala experiences encompassing spiritual intuition, messages from the unseen realm, and dream visualizations. These experiences hold strong potential as critical, contextual, and locally grounded social studies teaching resource for Grade VII, Chapter IV on Community Empowerment.